2022
DOI: 10.1155/2022/5036026
|View full text |Cite|
|
Sign up to set email alerts
|

A Deep Learning Filter that Blocks Phishing Campaigns Using Intelligent English Text Recognition Methods

Abstract: Most of the sophisticated attacks in the modern age of cybercrime are based, among other things, on specialized phishing campaigns. A challenge in identifying phishing campaigns is defining a classification of patterns that can be generalized and used in different areas and campaigns of a different nature. Although efforts have been made to establish a general labeling scheme in their classification, there is still limited data labeled in such a format. The usual approaches are based on feature engineering to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…19 Software methods for detecting phishing attacks are being developed. Software methods for detecting phishing attacks use techniques such as Blacklists, 20 Whitelists, 21 pattern or text matching methods, 22 visual similarity, 23 and machine and deep learning. 24 Deep and machine learning methods are rapidly gaining popularity in the field of cyber security and the detection of phishing attacks.…”
mentioning
confidence: 99%
“…19 Software methods for detecting phishing attacks are being developed. Software methods for detecting phishing attacks use techniques such as Blacklists, 20 Whitelists, 21 pattern or text matching methods, 22 visual similarity, 23 and machine and deep learning. 24 Deep and machine learning methods are rapidly gaining popularity in the field of cyber security and the detection of phishing attacks.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%